Exchange rate dynamics and trade balance in Somalia: An ARDL approach - Nur, Abdulkadir Mohamed; Ali, Ali Yassin Sheikh (Edelweiss Applied Science and Technology, 2025)
This study looks at how Somalia's trade balance has been affected by variations in the exchange rate, addressing the gap in empirical research on the relationship between macroeconomic variables and trade performance in fragile economies. The study used time series data sourced from the World Bank, SESRIC, the Central Bank of Somalia, and the IMF. The study employed augmented Dickey-Fuller tests and Phillips-Perron tests to assess the stationarity of the data. The study utilized an autoregressive distributed lag (ARDL) model to identify both short-term and long-term effects of exchange rate volatility on Somalia’s trade balance. The study found that over time, GDP, along with the real effective exchange rate (REER), had positive impacts on trade balances, whereas inflation rates and foreign direct investment (FDI) negatively influenced Somalia's trade balance in the long run. In the short term, there is a significant positive correlation between GDP, FDI, and REER and the trade balance, whereas the Consumer Price Index (CPI) has a negative impact. These are clear indications that any slight change in economic performance, changes in the value of money circulating, or inflation levels shall be reflected accordingly in Somalia’s trade balances. In terms of trade politics, the government of Somalia should focus on economic diversification, enhancing export competitiveness, and maintaining price stability to achieve sustainable trade and economic growth.